Relevance of interactive marketing practices for enhancing market performance: the case of soft drink manufacturing enterprises in Kigali city - Nimusima, Pereez; Kamukama, Nixon; Kalibwani, Rebecca; Rwakihembo, John (American Journal of Communication, 2022)
Purpose: The digital environment today has presented a great challenge for companies, locally and internationally on how they can leverage interactive marketing practices to maintain a warm relationship with their clients. The endless shifts in the customer journey map have made it, not only hard to manage customer experience, but also become more unpredictable. In due course, the imperative of complying with technology forces, to leverage customer patronage has put marketers to the task. The objective of the study was to establish the effect of interactive marketing practices on market performance of soft drink enterprises in Kigali City. Methodology: The study implemented a two-phase methodology that converged quantitative and qualitative methods to collect data. Simple random sampling technique was used to select 322 enterprises producing soft drinks in Kigali City which were later investigated using a self-report questionnaire and interview guide. To reduce the effect of the methods, the study collected evidence from both primary and secondary sources. Based on the response rate of 78%, the study carried out a validity and reliability check on 253 responses and used Pearson correlations and AMOS for analysis. Findings: The study established a positive and significant relationships between interactive marketing practices and market performance (r=.267, p<.01). 6.7% variations in market performance (Adjusted R Square=.067) was explained by interactive marketing practices. This finding shows that interactive marketing practices are relevant for soft drink firms in the region. Recommendation: On the basis of confirmed relationships, the study recommends that firms disseminate their marketing information using interactive marketing practices, since they cater for individual customer information needs and have multiplier effect on their purchase behavior. Whereas the mixed conceptual ambiguities that still exist in literature could have affected the conceptualization and therefore results, this study also merely tested direct relationships, future studies may seek to test mechanisms through which specific Interactive Marketing Practices influence performance in a none soft drink sector.
Keywords: Interactive Marketing; Soft drinks; Market performance; Digital marketing; Promotion